Using Guided Inquiry Learning with Tracker Application to Improve Students’ Graph Interpretation Ability - Sartika, Yuni; Wahyudi, Ismu; Abdurrahman, Abdurrahman (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2019)
The graph interpretation ability is an important ability for students in conducting physics experiments. The tracker application in straight motion topic can track objects precisely and accurately. This research aims to find out how the effect of tracker use on straight-motion learning based on guided inquiry on the ability of students' graph interpretation. The sample of this research is students of class X, in one of the State Senior High School in Bandar Lampung. The research design used was one group pretest-posttest. Learning is carried out by conducting guided inquiry-based straight-line experiment activities, then processing experimental data by analyzing experimental videos using tracker software. Data on students' interpretation ability is obtained using a test (pretest-posttest). Data analysis techniques for student learning outcomes using Paired Sample T-Test. Based on the results of the research obtained the average score of the ability to interpret the graph increased by 59.00% with a high mean of N-gain (0.71) at a 95% confidence level. These results indicate that learning by using a tracker can improve the ability to interpret graphics very well. Based on the test results obtained a significance of 0.000, which is less than 0.05, it can be concluded that there are significant differences in the ability of students to interpret graphics before and after learning using a tracker.